Altered IL-2 and IL-10 serum levels in schizophrenic patients - H.Frayyeh, Arkan; M. Jawad El-Saffar, Jenan (Iraqi Journal of Science, 2023)
Schizophrenia (SZ) is severe mental disorder and characterized by fundamental disturbances in thinking, perception and emotions. Immune deregulation has been postulated to be one of the mechanisms underlying the pathogenesis of schizophrenia. This study hypothesized that interleukins would have a link with schizophrenia patients. The serum IL-2 and IL-10 levels were examined by enzyme-linked immunosorbent assay (ELISA) in schizophrenia patients (n=60) and healthy controls (n = 30). The results showed that serum IL-2 and IL-10 levels were significantly different among schizophrenia patients. The observations indicate a significant decrease (P < 0.05) in schizophrenic patients serum levels of IL-2 compared with healthy control. Whereas detection of IL-10 in the schizophrenic patients serum showed significantly increase level (P < 0.05) compared with healthy control. The results supported that immune disturbance is related to the schizophrenia patients and might play an important role in the pathophysiology of schizophrenia.